L’Institutionnalisation de l’histoire de l’art en France au XIXe siècle - Therrien, Lyne (RACAR : Revue d'art canadienne / Canadian Art Review, 2001)
This article examines the beginnings of art history instruction in France in a wide range of institutions of higher, or specialized, learning, as they relate to the disciplines introduction in the university. These other sites included the Collège de France, founded in the sixteenth century; the École des chartes, specializing in the analysis of historic documents; the École des Beaux-Arts and the École du Louvre; state-sponsored schools of archaeology in Athens and in Rome; and the École Pratique des Hautes Études which, from the 1860s, offered seminars in archaeology. A substantial body of scholarship was also produced through individual research and archaeological networks like that initiated by Arcisse de Caumont, though Émile Mâle claimed in 1894 that this corpus remained unknown in the university setting.However unevenly, the process of disciplinary formation was one that unfolded from without to within the university as it was articulated across institutions with divergent missions and organizational forms. As an emergent field within the university, the position of art history was marked by relations both of dependence and tension in regard to classical archaeology. Ancient art figured earliest in university art history teaching because of its links with the humanist tradition and the discipline of history. The art of the Middle Ages, the Renaissance and, eventually, later periods gained legitimacy in the university under the aegis of history. Crucial here was recognition granted by university historians in enabling art history to achieve status as a separate discipline, characterized by its own methods, beside the fields of history and philosophy.